The Effectiveness of Civics Education in Applying Social Attitudes to Address Student Delinquency at Supian Membangun Silangkitang Vocational School - Dewi Yuliana; Junita Junita (IKIP Mataram, 2023)
This study aims to determine the effectiveness of teaching Pancasila and Citizenship Education (PPKN) in applying social attitudes as an effort to overcome student delinquency in class XI SMK Supian Bangun Silangkitang. The method used is qualitative with a descriptive approach. The research subjects consisted of five students (three girls and two boys) who were chosen because they were assumed to have sufficient ability and knowledge to answer questions and were willing to be interviewed. Data collection techniques include observation, interviews, and documentation studies. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the study show that there are three important activities in teaching PPKN that are effective for tackling student delinquency, namely managing classes, delivering material, and applying relevant learning methods. Teachers must also include indicators of social attitudes such as honesty, courtesy, confidence, and discipline in teaching. In the context of teaching PPKN, students' social attitudes can be said to be very good. Thus, the results of this study can provide input for teachers and related parties in increasing the effectiveness of PPKN teaching in applying social attitudes to overcome student delinquency at Supian Bangun Silangkitang Vocational School.